Bahan Bakar Padat Dari Pelepah Sawit Menggunakan Proses Karbonisasi Dengan Variasi Ukuran Bahan Baku Dan Suhu - Qurotullaili Qurotullaili; Komalasari Komalasari; Zuchra Helwani (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Palm frond so far only used as a source of raw materials for animal feed, compost and organic fertilizer in the plantation. Palm frond has a calorific value of 15,184.05 kJ/kg. Utilization of palm frond as main material of solid fuel production with carbonization process can reduce the problem of oil palm plantations waste and can be increased the calorific value of product. The aims of this study is to produce solid fuel from palm fronds by using carbonization process and analyze solid fuel quality from palm frond with variation of raw material size and temperature. Variation of carbonization temperature were 450°C, 500°C and 550°C. Variation of raw material size 1.68 – 2.38 mm (-8 +10 mesh), 0.84 – 1 mm (-16 +20 mesh) and 0.42 – 0.5 mm (-32 +35 mesh). Water content were 3.66 – 4.86%, ash were 9.39 – 16.17%, volatile were 9.45 – 28.60% and fixed carbon were 57.26 – 70.01%. The highest caloric value was 28,410.94 kJ/kg for 550°C of carbonization temperature and 0.42 – 0.5 mm (-32 +35 mesh) of raw material size.Keywords : biomass, caloric value,carbonization, palm frond